PSO-Optimized Lithology-Guided Deep Learning Model for Uniaxial Compressive Strength Prediction from Well Logs - Liuyi Xiao; Hu Zheng; Muhammad Ali; Wakeel Hussain; Minyi Zhu; Sayed Muhammad Iqbal; Altaf Hussain; Mohsin Ali (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Explainable machine learning for predicting building energy performance and sustainability certification in construction megaprojects - Li Ma; Muhammad Sumair Ghouri; Muhammad Altaf; Mingxing Zheng; Liang Wang (Energy and Buildings, 2026)

Revisiting iron nutrition: a nano–organic approach for enhanced wheat yield, antioxidant resilience, and photosynthetic pigments - Hafiz Muhammad Jhanzab; Farhat Yasmeen; Ayshah Aysh Alrashidi; Muhammad Tanveer Altaf; Riaz Ahmad; Mohamed Ebaid; Ammar AL-Farga (Cereal Research Communications, 2026)

Engineered Adsorbents for Microplastic Mitigation: From Interfacial Mechanisms to Scalable Environmental Perspectives - Hammad Sajjad; Waleed Altaf; Ramika Javaid; Tehreem Fakhra; Muhammad Hayat; Ammar bin Yousaf; Nadeem Raza; Suryyia Manzoor; Lilia Basilio de Caland (Journal of Environmental Chemical Engineering, 2026)

MOF-based composite catalysts for CO2 reduction: Recent advances and perspectives - Asad Ur Rehman; Syed Shoaib Ahmad Shah; Sami Ullah; Arooj Fatima; Ibrahim A. Shaaban; Muhammad Sufyan Javed; Awais Ahmad; Muhammad Altaf Nazir (Environmental Research, 2026)

Harnessing biostimulants to alleviate potentially toxic element stress in vegetable crops - Amna Jamil; Waqas Liaqat; Asia Maqbool; Pramod Sargar; Muhammad Anwar-Ul-Haq; Shraddha Samindre; Muhammad Faheem Jan; Faheem Shehzad Baloch; Heba I. Mohamed; Muhammad Tanveer Altaf (Planta, 2026)

Geospatial Assessment of Freshwater Quality for Heavy Metals and its Potential Health Risks Using Geoinformatics and Water Index Models in Gilgit-Baltistan-Pakistan - Naila Jabeen; Lubna Ghazal; Humaira Kanwal; Tayyab Raza Fraz; Muhammad Farrakh Nawaz; Liaquat Karim; Faten Khalid Karim; Samih M. Mostafa; Altaf Hussain Lahori (International Journal of Environmental Research, 2026)
Access to safe drinking water is a growing global challenge, with billions of people exposed to water scarcity and contamination risks. Heavy metals in drinking water are of particular concern due to their toxic effects on human health and ecosystems. This study assessed the drinking water quality of Hunza Valley, Gilgit-Baltistan, Pakistan, where no comprehensive geospatial evaluation had previously been conducted. A total of 66 water samples from springs and glaciers were analyzed for physico-chemical parameters and heavy metals (Fe, Ni, Cd, Cr-VI, As, and Pb). Statistical analysis (correlation, principal component analysis and cluster analysis), water quality indices (Water Quality Index and Synthetic Pollution Index), human health risk assessment (Hazard Quotient and Hazard Index) and geostatistical interpolation (Ordinary Kriging) were employed. Results showed that As (77%), Pb (34%), Cd (25%), and Cr-VI (9%) exceeded WHO limits, while Fe and Ni remained within permissible levels. WQI classified 59% of samples as unfit for human consumption, while SPI designated 26% as unsafe. PCA extracted four significant factors explaining 67% of total variance, and hotspot mapping highlighted Aliabad, Dorkhun, and Ganish as most contaminated villages. The hazard quotient and hazard index for non-carcinogenic health risk showed very few samples with significant health risk. The geospatial maps of health risk showed higher geospatial variability for arsenic, lead and iron whereas low variations were observed for cadmium, chromium and nickel. The TCRI values revealed As, Cd, Cr, Pb and Ni pose significant carcinogenic health risk with geospatial variation highlighting the western side of the district. The findings emphasize the urgent need for feasibility studies for treatment facilities, regular monitoring, cancer specific health risk studies to protect public health in Hunza Valley. This research provides a framework for sustainable water management aligned with SDG-6.

Elicitors in Plant Defense: Exploring Their Role in Biotic and Abiotic Stress Resistance - Muhammad Tanveer Altaf; Waqas Liaqat; Muhammad Aneeq Ur Rahman; Chidera Anuforo; Asia Maqbool; Amjad Ali; Muhammad Faheem Jan; Muhammad aasim; Heba I. Mohamed; Faheem Shehzad Baloch (Journal of Plant Growth Regulation, 2026)

Genetic Diversity and Population Structure of 72 Turkish Ficus carica (L.) Genotypes Assessed Using SCoT Markers - Meliha Feryal Sarıkaya; Muhammad Azhar Nadeem; Sarmad Ali Qureshi; Mehmet Bedir; Muhammed Tatar; Amjad Ali; Muhammad Tanveer Altaf; Viyan Acar Uçer; Kağan Kökten; Erdal Aglar; Faheem Shehzad Baloch (Biochemical Genetics, 2026)

Rock–phosphate–enriched hydrochars derived from organic wastes: a sustainable amendment for multi-metal contaminated soil - Altaf Hussain Lahori; Monika Mierzwa-Hersztek; Nguyen Thi Lam; Sergij Vambol; Muhammad Iftikhar Hussain; Said Ali Akbar (Waste Management, 2026)

Nanoparticles in Vegetable Production: From Soil to Human Health - Amna Jamil; Muhammad Tanveer Altaf; Ishtiaq Ahmad; Waqas Liaqat; Asia Maqbool; Muhammad Anwar-Ul-Haq; Pramod Sargar; Heba I. Mohamed; Faheem Shehzad Baloch (Water, Air, & Soil Pollution, 2026)

Silver-decorated ZnO nanorods for sunlight-assisted photocatalytic degradation of ciprofloxacin, methyl orange, and 2,4-dinitrophenol in water - Iqra Mazhar; Muhammad Afzaal; Muhammad Altaf; Manzar Sohail; Raja Shahid Ashraf; Abdul-Sattar Nizami (Nanotechnology for Environmental Engineering, 2026)

Iron-Loaded Biochar Ameliorates Cadmium-Induced Phytotoxicity in Rapeseed by Modulating Cd Uptake, Nutrient Homeostasis, and Antioxidative Systems - Sumra Siddique Abbasi; Hafiz Saqib Hayat; Hua-Yi Chen; Muhammad Mohsin Altaf; Mudawi M. Nour; Afrah E. Mohammed (Journal of Soil Science and Plant Nutrition, 2026)

Precision Agriculture Through Green Nanoparticles: Mechanistic Insights into Nutrient Delivery and Enzyme-Targeted Pest Control with Emerging Computational Perspectives - Muhammad Irfan; Hira Altaf; Mishal Naveed; Nadia Zeeshan; Umer Rashid; Amber Afroz (Journal of Soil Science and Plant Nutrition, 2026)

Unveiling Morpho-Anatomical Strategies of Cenchrus Ciliaris L. for Survival under Vehicular Pollution Stress - Hafiz Muhammad Mohsin Hassan; Muhammad Akram; Imran Haider; Muhammad Altaf Nazir; Lamy Hamed; Abdullateef Al-Saeed; ElSayed A. Badr; Ahmed Ismail (Water, Air, & Soil Pollution, 2026)

Enhancing phytoextraction efficiency of king grass through foliar application of plant growth regulators under cadmium and chromium stress - Muhammad Mohsin Altaf; Xuezhi Dong; Meng Wang; Xiaoyan Sun; Dong Li; Zhiqiang Zhu (Plant Cell Reports, 2026)

Combatting vanadium toxicity in rapeseed (Brassica napus L.) via soil amendment and foliar application of calcium oxide nanoparticles: insights into physio-biochemical and antioxidant defense mechanisms - Muhammad Mohsin Altaf; Afrah E. Mohammed; Modhi O. Alotaibi; Motirh Al-Mutairi; Jun Wang (Plant Cell Reports, 2026)

Retraction notice to “Borage leaf extract improves the vase life of cut gladiolus flowers by delaying the senescence process and reducing water stress” [Postharvest Biol. Technol. 210 (2024) 112766] - Faisal Zulfiqar; Anam Moosa; Antonio Ferrante; Anastasios Darras; Mohamed S. Sheteiwy; Baber Ali; Muhammad Ahsan Altaf; Walid Soufan; Ayman El Sabagh (Postharvest Biology and Technology, 2026)

Aqueous phase recirculation in hydrothermal liquefaction: A critical review - Ayaz Ali Shah; Muhammad Ilyas Khan; Altaf Alam Noonari; Abdul Sattar Jatoi; Judit Sandquist (Biomass and Bioenergy, 2026)

Molecular mechanisms of heavy metal uptake, accumulation, and tolerance in sweet potato (Ipomoea batatas): implications for phytoremediation and food safety - Muhammad Shahid; Muhammad Mohsin Altaf; Muhammad Ahsan Altaf; Rafiq Ahmad; Kashif Khan; Cheng-cheng Si (Plant and Soil, 2026)

Exogenous γ-Aminobutyric acid alleviates chromium phytotoxicity by activating the antioxidant defense mechanism and oxidative stress tolerance in pepper seedlings - Liping Zhang; Xiaoyue Wang; Yanhui Yang; Xiangrui Li; Muhammad Ahsan Altaf; Zhiwei Wang (Plant and Soil, 2026)

Validation and pharmacological evaluation of bioactive constituents from Silybum marianum seeds (milk thistle) using in vitro and in silico approaches - Muhammad Tahir Akhtar; Uzma Altaf; Taleeha Roheen; Tahira Almas; Rahman Qadir; Mubshara Saadia (In Silico Pharmacology, 2026)

MOF/Graphene interfaces in catalytic water splitting: Recent breakthroughs and future outlook - Asad Ur Rehman; Muhammad Asghar; Abdul Rauf; Tayyaba Najam; Ibrahim A. Shaaban; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Fuel, 2026)

Genome-wide identification of RCC1 gene family in pepper (Capsicum annuum L.) and functional analysis of CaRCC1-16 under heat stress - Nadia Sajjad; Tayeb Muhammad; Altaf Hussain; Yong Kang; Qiaomin Yang; Mahnoor Khattak; Minghui Lu (Plant Cell Reports, 2026)

Quantifying key drivers of atmospheric methane across Pakistan using a machine learning approach - Farzana Altaf; Toqeer Muhammad; Shahid Nadeem; Asif Sajjad; Mazhar Iqbal (Environmental Monitoring and Assessment, 2026)

Carboxymethyl cellulose: Structural modifications and their impact on barrier and mechanical properties for sustainable food packaging - Batool Esmat; Shumaila Bibi; Mohamed Mohamed Soliman; Hamdy Khamees Thabet; Muhammad Ahmad Wattoo; Muhammad Altaf Nazir; Zeinhom M. El-Bahy; Aziz ur Rehman (Journal of Stored Products Research, 2026)

Dual photo/electrocatalytic CO2 reduction by porphyrin based metal organic framework under visible light and electrochemical bias - Mamuna Aslam; Uzma Saleem; Ibrahim A. Shaaban; Tahani Rahil Aldhafeeri; Ataf Ali Altaf; Muzammil Iqbal; Muhammad Tariq; Mohammed A. Assiri; Shahid Hussain; Hafiz Muhammad Asif (Fuel, 2026)

Synergistic Ni single-atom–nanoparticle interfaces for poison-resistant CO₂ electroreduction - Syed Shoaib Ahmad Shah; Jamal Kazmi; Muhammad Altaf Nazir; Manzar Sohail; Muhammad Sufyan Javed; Tayyaba Najam; Lishan Peng; Ramón A. Alvarez-Puebla (Chemical Engineering Journal, 2026)

Recent progress of metallic nanomaterials in energy, biomedical and environment sector - Kinza Maqsood; Sami Ullah; Asad ur Rehman; Hafsa Bashir; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Next Research, 2025)

Geospatial mapping of potential aggregate resources using integrated GIS-AHP, geotechnical, petrographic and machine learning approaches - Javid Hussain; Nafees Ali; Xiaodong Fu; Jian Chen; Sayed Muhammad Iqbal; Altaf Hussain; Hikmat Salam (Earth Science Informatics, 2025)

From global challenges to specific solutions: climate change impacts on agriculture with a focus on sorghum through bibliometric analysis - Waqas Liaqat; Muhammad Tanveer Altaf; Muhammad Faheem Jan; Haseeb Ahmad; Ehtisham Hassan Khan; Celaleddin Barutçular; Gönül Cömertpay; Faheem Shehzad Baloch; Heba I. Mohamed (Cereal Research Communications, 2025)

Endophytic fungi as biocontrol agents: A metabolite-driven approach to crop protection and sustainable agriculture - Muhammad Faiq; Amjad Ali; Shazia Shafique; Sobiya Shafique; Allah Rakha Yaseen; Rimsha Fatima; Muhammad Tanveer Altaf; Faheem Shehzad Baloch (Physiological and Molecular Plant Pathology, 2025)

Next-generation strategies for nitrogen-efficient maize production for a greener tomorrow - Muhammad Faheem Jan; Waqas Liaqat; Muhammad Tanveer Altaf; Muhammad Dawood Ahmadzai; Asia Maqbool; Faheem Shehzad Baloch; Ming Li (Field Crops Research, 2025)

Corrigendum to “Integrated reservoir characterization and simulation approach to enhance production of tight sandstone gas reservoir, Sulige gas field, Ordos Basin, China”[Phys. Chem. Earth, Parts A/B/C 138 (2025) 103846, 1-17 103846] - Sayed Muhammad Iqbal; Dawei Hu; Javid Hussain; Nafees Ali; Wakeel Hussain; Altaf Hussain; Edwin E. Nyakilla (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Bimetallic metal-organic frameworks as versatile electrocatalysts for water splitting in neutral and alkaline environments - Syed Arfan Haider; Tehseen Mushtaq; Bakhtawar Sajjad; Munazza Shahid; Muhammad Altaf; Ayman Nafady; Ghayoor Abbas Chotana; Manzar Sohail; Shahid Rasul; Raja Shahid Ashraf (Fuel, 2025)

Recent advances in layered double hydroixdes@MXene (LDHs@MXene) composites: Synthesis, properties, and catalytic applications - Sundas Riaz; Sami Ullah; Sanam Bashir; Aziz ur Rehman; Rashid Iqbal; Tayyaba Najam; Mostafa A. Ismail; Md Rezaul Karim; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Applied Clay Science, 2025)

Retraction Note: Melatonin-Polyamine Interplay in the Regulation of Stress Responses in Plants - Rahul Kumar Tiwari; Ravinder Kumar; Milan Kumar Lal; Awadhesh Kumar; Muhammad Ahsan Altaf; Rajni Devi; Vikas Mangal; Safina Naz; Muhammad Mohsin Altaf; Abhijit Dey; Tariq Aftab (Journal of Plant Growth Regulation, 2025)

Approaches for the amelioration of adverse effects of drought stress on soybean plants: from physiological responses to agronomical, molecular, and cutting-edge technologies - Muhammad Faheem Jan; Muhammad Tanveer Altaf; Waqas Liaqat; Changzhuang Liu; Heba I. Mohamed; Ming Li (Plant and Soil, 2025)

Jasmonic Acid as a Regulator in Plant Stress Tolerance: Mechanisms and Agricultural Implications - Jalil Ahmad; Faisal Hayat; Ummara Khan; Muhammad Ahsan Altaf; Muhammad Ahmad; Muhammad Tahir Akram; Karthishwaran Kandhan; Mohamed S. Sheteiwy; Juan Li; Mohammed Alyafei (Journal of Crop Health, 2025)

Genome-wide analysis of the UFGT gene family in colored cotton: evolution, structure and expression patterns - Jaweria Iqbal; Muhammad Tanveer Altaf; Waqas Malik; Abdul Qayyum (Genetic Resources and Crop Evolution, 2025)

A Bayesian framework for crop model calibration: A case study in the US Corn Belt - Matteo G. Ziliani; Muhammad U. Altaf; Trenton E. Franz; Bangyou Zheng; Scott Chapman; Justin Sheffield; Ibrahim Hoteit; Matthew F. McCabe (European Journal of Agronomy, 2025)

Integrated reservoir characterization and simulation approach to enhance production of tight sandstone gas reservoir, Sulige gas field, Ordos Basin, China - Sayed Muhammad Iqbal; Dawei Hu; Javid Hussain; Nafees Ali; Wakeel Hussain; Altaf Hussain; Edwin E. Nyakilla (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Exploring genetic diversity of Turkish fig (Ficus carica L.) germplasm using inter-Primer Binding Site (iPBS) retrotransposon markers - Viyan Acar Uçer; Erdal Aglar; Parnaz Mortazavi; Sarmad Ali Qureshi; Amjad Ali; Muhammed Tatar; Muhammad Tanveer Altaf; Mehmet Bedir; Sezai Ercişli; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)

Chlorophyll fluorescence: a smart tool for maize improvement - Muhammad Faheem Jan; Ming Li; Waqas Liaqat; Muhammad Tanveer Altaf; Changzhuang Liu; Haseeb Ahmad; Ehtisham Hassan Khan; Zain Ali; Celaleddin Barutçular; Heba I. Mohamed (Cereal Research Communications, 2025)

Advancing Chickpea Breeding: Omics Insights for Targeted Abiotic Stress Mitigation and Genetic Enhancement - Muhammad Tanveer Altaf; Waqas Liaqat; Amjad Ali; Amna Jamil; Muhammad Fahad; Muhammad Aneeq Ur Rahman; Faheem Shehzad Baloch; Heba I. Mohamed (Biochemical Genetics, 2025)

Molecular screening of diverse Tomato germplasm for root-knot nematode resistance using the Mi23 marker - Parnaz Mortazavi; Amjad Ali; Muhammed Tatar; Fatih Ölmez; Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Hayriye Yildiz Dasgan; Boran Ikiz; Tuğçe Temtek; Ömer Faruk Bilgin; Ayşe Mücahitoğlu; Mahmut Bayram; et al. (Physiological and Molecular Plant Pathology, 2025)

Exploring the phytochemical profile, antioxidant activity, and anticancer potential of Achillea millefolium extracts: In-vitro and in-silico investigation - Asia Kiran; Awais Altaf; Muhammad Sarwar; Tahir Maqbool; Muhammad Abdul Basit Ashraf; Muhammad Naveed; Tariq Aziz; Metab Alharbi (South African Journal of Botany, 2025)

The induction of polyamines metabolism pathway and membrane stability with silicon alleviate the vanadium toxicity in pepper plants - Naveed Mushtaq; Muhammad Ahsan Altaf; Huangying Shu; Xu Lu; Shanhan Cheng; Mohamed A. El-Sheikh; Parvaiz Ahmad; Huizhen Fu; Zhiwei Wang (Journal of Hazardous Materials, 2025)

Development of tetraploids in tissue culture: modern techniques and biotechnological innovations - Sabeen Rehman Soomro; Salma Naimatullha Soomro; Muhammad Tanveer Altaf; Waqas Liaqat; Muhammad Azhar Nadeem; Faheem Shehzad Baloch; Muhammad Aasim; Heba I. Mohamed (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Exploring environmentally stable and novel genetic factors influencing rice grain shape and yield attributes - Sadia Gull; Zulqarnain Haider; Houwen Gu; Saleem Uddin; Muhammad Qasim; Rana Ahsan Raza Khan; Adil Altaf; Sajid Fiaz; Mona S. Alwahibi; Mohamed S. Elshikh; Rashid Iqbal; Jun Miao; et al. (Euphytica, 2025)

Applicability of Start Codon Targeted (SCoT) markers for the assessment of genetic diversity in bread wheat germplasm - Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Amjad Ali; Waqas Liaqat; Mehmet Bedir; Nurettin Baran; Aleksandra Ilić; Muhammad Kashif Ilyas; Abdul Ghafoor; Hamide Dogan; Muhammad Aasim; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)
Research endeavors focused on examining genetic diversity play a pivotal role in advancing agricultural practices, as they furnish valuable insights for breeding programs and the preservation of germplasm. Wheat holds significant global importance as a cereal crop, serving as a primary source of sustenance for almost one-third of the global human population. In the current study, a total of 80 bread wheat genotypes were characterized using the start codon targeted (SCoT) marker system. A set of 14 polymorphic primers yielded a cumulative count of 399 bands with an average of 28.05 bands per primer. The range of diversity markers, such as polymorphism information content (0.26–0.59), effective numbers of alleles (1.27–1.59), Shannon’s information index (0.30–0.51), and gene diversity (0.18–0.34), provided evidence of elevated genetic differences within the examined germplasm. According to the findings of the molecular variance analysis, greater genetic variations are found within populations (92%). The model-based structural approach partitioned the 80 bread wheat genotypes into two distinct populations (Population A and B). The diversity indices based on the structures of the populations revealed that population A had greater diversity compared to population B. Both the principal coordinate analysis and the neighbor-joining analysis also differentiated the 80 different bread wheat genotypes based on their respective collection points. The present crop diversity offers great opportunities for enhancing crop quality and increasing tolerance to environmental challenges, both of which will lead to a reduction in the problem of food insecurity.

Management of the lignocellulosic structure of agricultural straw and improving energy productivity - Altaf Alam Noonari; Muhammad Safar Korai; Munawar Ali Pinjaro; Ghulam Shabir Solangi; Arthur J. Ragauskas (Environment, Development and Sustainability, 2024)

Regional distribution differences of antibiotics in tropical marine aquaculture area: Insights into antibiotic management and risk assessment - Xiaoyu Ren; Yongqiang Qin; Yankun Zhang; Jia Xie; Xiaoping Diao; Muhammad Mohsin Altaf (Science of The Total Environment, 2024)

Microbial-inoculated biochar for remediation of salt and heavy metal contaminated soils - Hafiz Muhammad Mazhar Abbas; Ummah Rais; Muhammad Mohsin Altaf; Fahd Rasul; Asad Shah; Ashar Tahir; Muhammad Nafees-Ur-Rehman; Muhammad Shaukat; Haider Sultan; Ruilong Zou; Mohammad Nauman Khan; Lixiao Nie (Science of The Total Environment, 2024)

Applicability of SCoT markers in unraveling genetic variation and population structure among sugar beet (Beta vulgaris L.) germplasm - Nazlı Aybar Yalinkiliç; Sema Başbağ; Muhammad Tanveer Altaf; Amjad Ali; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Molecular Biology Reports, 2024)

Mechanistic Concepts of Multifaceted Roles of Neurotransmitters Like Signalling Molecules in Plant Responses to Biotic Stress - Ritul Saharan; Sudeepta Pattanayak; Rajendran Poorvasandhya; Jagmohan Singh; Priyanka Lal; Muhammad Ahsan Altaf; Awadhesh Kumar; Milan Kumar Lal; Rahul Kumar Tiwari; Ravinder Kumar (The Botanical Review, 2024)

In Silico Identification and Characterization of Rare Cold Inducible 2 (RCI2) Gene Family in Cotton - Muhammad Fahad; Leeza Tariq; Muhammad Tanveer Altaf; Muhammad Shahnawaz; Mudassir Aslam; Waqas Liaqat; Inayat Ullah; Izhar Ullah; Heba I. Mohamed; Abdul Basit (Biochemical Genetics, 2024)

Role of pressmud compost for reducing toxic metals availability and improving plant growth in polluted soil: Challenges and recommendations - Altaf Hussain Lahori; Maira Tunio; Samreen Riaz Ahmed; Monika Mierzwa-Hersztek; Viola Vambol; Ambreen Afzal; Anila Kausar; Sergij Vambol; Aqsa Umar; Atif Muhammad (Science of The Total Environment, 2024)

Enhancing mango yield and soil health with organic and slow-release fertilizers: A multifaceted evaluation - Yangqiu Jiao; Xiaoyan Sun; Xuezhi Dong; Jing Yin; Zhidong Li; Kailu Zhang; Muhammad Mohsin Altaf; Dong Li; Zhiqiang Zhu (Science of The Total Environment, 2024)

Exploring the role of γ-Oryzanol on stabilization mechanism of Pickering emulsion gels loaded by α-Lactalbumin or β-Lactoglobulin via multiscale approaches - Jinzhe Li; Qiuwan Jiang; Heyang Xu; Meng Li; Muhammad Altaf Hussain; Zhanmei Jiang; Juncai Hou (Food Chemistry, 2024)

Corrigendum to “Exploring the role of γ-Oryzanol on stabilization mechanism of Pickering emulsion gels loaded by α-Lactalbumin or β-Lactoglobulin via multiscale approaches” [Food Chemistry 457 (2024) 140096] - Jinzhe Li; Qiuwan Jiang; Heyang Xu; Meng Li; Muhammad Altaf Hussain; Zhanmei Jiang; Juncai Hou (Food Chemistry, 2024)

Strategies and bibliometric analysis of legumes biofortification to address malnutrition - Muhammad Tanveer Altaf; Waqas Liaqat; Amna Jamil; Muhammad Faheem Jan; Faheem Shehzad Baloch; Celaleddin Barutçular; Muhammad Azhar Nadeem; Heba I. Mohamed (Planta, 2024)

Recent advances of MXene@MOF composites for catalytic water splitting and wastewater treatment approaches - Samreen Afzal; Aziz ur Rehman; Tayyaba Najam; Ismail Hossain; Mostafa A.I. Abdelmotaleb; Sundas Riaz; Md Rezaul Karim; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Chemosphere, 2024)

A Bibliometric Analysis of Genome-wide Association Study (GWAS) and Sorghum (Sorghum bicolor L) Based on Web of Science Using VOS Viewer - Muhammad Tanveer Altaf; Waqas Liaqat; Amna Jamil; Muhammad Faheem Jan; Faheem Shehzad Baloch; Heba I. Mohamed (Journal of Soil Science and Plant Nutrition, 2024)

A Critical Review: Breeding Objectives, Genomic Resources, and Marker-Assisted Methods in Sorghum (Sorghum bicolor L.) - Muhammad Tanveer Altaf; Waqas Liaqat; Amna Jamil; Heba I. Mohamed; Muhammad Fahad; Muhammad Faheem Jan; Faheem Shehzad Baloch (Journal of Soil Science and Plant Nutrition, 2024)

Light-driven C1 Chemical Conversion with LDH-based Nanomaterials - Zixi Liu; Muhammad Altaf Nazir; Muhammad Altaf; Hammad Majeed; Zeinhom M. El-Bahy; Mohamed H. Helal; Abdul Rauf; Sami Ullah; Tayyaba Najam; Syed Shoaib Ahmad Shah; Aziz ur Rehman (Applied Clay Science, 2024)

Recent physiological and molecular approaches of abiotic stress tolerance in plants - Anis Ali Shah; Muhammad Ahsan Altaf; Rehana Sardar (Brazilian Journal of Botany, 2024)

Silicon oxide nanoparticle mitigated the vanadium toxicity in Cucumber (Cucumis sativus L.) - Muhammad Mohsin Altaf; Sahrish Ashraf; Muhammad Qaisar Naeem Khan; Sibgha Noreen; Muhammad Anwar; Rafa Almeer; Rattandeep Singh; Atique ur Rehman (South African Journal of Botany, 2024)

Melatonin induced reversibility of vanadium toxicity in muskmelon by regulating antioxidant defense and glyoxalase systems - Muhammad Mohsin Altaf; Zoia Arshad Awan; Sahrish Ashraf; Muhammad Ahsan Altaf; Zhiqiang Zhu; Abdulaziz Abdullah Alsahli; Parvaiz Ahmad (Journal of Hazardous Materials, 2024)

Comparative role of charcoal, biochar, hydrochar and modified biochar on bioavailability of heavy metal(loid)s and machine learning regression analysis in alkaline polluted soil - Altaf Hussain Lahori; Samreen Riaz Ahmed; Monika Mierzwa-Hersztek; Madiha Afzal; Ambreen Afzal; Shella Bano; Maria Taj Muhammad; Aqsa Aqsa; Viola Vambol; Sergij Vambol (Science of The Total Environment, 2024)

Drought stress in sorghum: physiological tools, breeding technology, Omics approaches and Genomic-assisted breeding -A review - Waqas Liaqat; Muhammad Tanveer Altaf; Celaleddin Barutçular; Heba I. Mohamed; Zain Ali; Muhammad Owais Khan (Journal of Soil Science and Plant Nutrition, 2024)

The chemical composition and biological activities of plant essential oils against Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) - Nimra Altaf; Muhammad Irfan Ullah; Muhammad Arshad; Muhammad Afzal; Laila A. Al‑Shuraym; Naunain Mehmood; Zafar Hayat; Samy M. Sayed (Journal of Plant Diseases and Protection, 2024)

Melatonin alleviates cadmium phytotoxicity through regulation of growth, photosynthesis, and antioxidant potential in two pepper genotypes - Muhammad Saqib; Umbreen Shahzad; Zakia Abid; Faisal Zulfiqar; Rahul Kumar Tiwari; Milan Kumar Lal; Waleed Amjad Khan; Mohamed A. El-Sheikh; Muhammad Ahsan Altaf (Acta Physiologiae Plantarum, 2024)

From stress to success: Silicon and nano-silicon strategies for enhancing fruit yield and quality in cadmium-exposed trees - Riaz Ahmad; Hafiza Muniba Din Muhammad; Safina Naz; Rahul Kumar Tiwari; Milan Kumar Lal; Parvaiz Ahmad; Muhammad Ahsan Altaf (South African Journal of Botany, 2024)

RETRACTED: Borage leaf extract improves the vase life of cut gladiolus flowers by delaying the senescence process and reducing water stress - Faisal Zulfiqar; Anam Moosa; Antonio Ferrante; Anastasios Darras; Mohamed S. Sheteiwy; Baber Ali; Muhammad Ahsan Altaf; Walid Soufan; Ayman El Sabagh (Postharvest Biology and Technology, 2024)

Exogenous strigolactone enhanced the drought tolerance of pepper (Capsicum chinense) by mitigating oxidative damage and altering the antioxidant mechanism - Huangying Shu; Kaijing Xu; Xiangrui Li; Jiancheng Liu; Muhammad Ahsan Altaf; Huizhen Fu; Xu Lu; Shanhan Cheng; Zhiwei Wang (Plant Cell Reports, 2024)

Biochar: Black Gold for Sustainable Agriculture and Fortification Against Plant Pathogens—A Review - Usman Arshad; Muhammad Tanveer Altaf; Waqas Liaqat; Muhammad Ali; Muhammad Nadeem Shah; Muhammad Jabran; Muhammad Amjad Ali (Journal of Crop Health, 2024)

Role of melatonin in the regulation of abiotic stress in plants - Muhammad Ahsan Altaf; Milan Kumar Lal; Rahul Kumar Tiwari (South African Journal of Botany, 2024)

Unlocking Triticum aestivum L. resilience: Exogenous proline's remarkable role in mitigating lead stress, and delving into the secrets of TaGSK1 gene expression - Sidra Balooch; Sibgha Noreen; Seema Mahmood; Nida Zahra; Ahmad Azeem; Muhammad Mohsin Altaf; Muhammad Salim Akhter; Adeel Abbas (South African Journal of Botany, 2024)

Distribution characteristics of antibiotic resistance genes and microbial diversity in the inshore aquaculture area of Wenchang, Hainan, China - Yongqiang Qin; Xiaoyu Ren; Yankun Zhang; Hanye Ju; Jin Liu; Jia Xie; Muhammad Mohsin Altaf; Xiaoping Diao (Science of The Total Environment, 2024)

Effect of EDDS on the rhizosphere ecology and microbial regulation of the Cd-Cr contaminated soil remediation using king grass combined with Piriformospora indica - Haixiang Zhang; Kailu Zhang; Yali Duan; Xiaoyan Sun; Li Lin; Qianli An; Muhammad Mohsin Altaf; Zhiqiang Zhu; Fan Liu; Yangqiu Jiao; Jing Yin; Can Xie; et al. (Journal of Hazardous Materials, 2024)

Sorghum: a Star Crop to Combat Abiotic Stresses, Food Insecurity, and Hunger Under a Changing Climate: a Review - Waqas Liaqat; Muhammad Tanveer Altaf; Celaleddin Barutçular; Heba I. Mohamed; Haseeb Ahmad; Muhammad Faheem Jan; Ehtisham Hassan Khan (Journal of Soil Science and Plant Nutrition, 2024)

Ultraviolet-B radiation in relation to agriculture in the context of climate change: a review - Waqas Liaqat; Muhammad Tanveer Altaf; Celaleddin Barutçular; Hira Nawaz; Izhar Ullah; Abdul Basit; Heba I. Mohamed (Cereal Research Communications, 2024)

Recent trends in wastewater treatment by using metal-organic frameworks (MOFs) and their composites: A critical view-point - Syed Shoaib Ahmad Shah; Manzar Sohail; Ghulam Murtza; Amir Waseem; Aziz ur Rehman; Iftikhar Hussain; Muhammad Sohail Bashir; Saleh S. Alarfaji; Ahmed M. Hassan; Muhammad Altaf Nazir; Muhammad Sufyan Javed; Tayyaba Najam (Chemosphere, 2024)

Utilizing thiourea-modified biochars to mitigate toxic metal pollution and promote mustard (Brassica campestris) plant growth in contaminated soils - Irfan Saleem; Samreen Riaz Ahmed; Altaf Hussain Lahori; Monika Mierzwa-Hersztek; Shella Bano; Ambreen Afzal; Maria Taj Muhammad; Madiha Afzal; Viola Vambol; Sergij Vambol; Zengqiang Zhang (Journal of Geochemical Exploration, 2024)

Land cover changes and carbon dynamics in Central India's dry tropical forests: A 25-year assessment and nature-based eco-restoration approaches - Tarun Kumar Thakur; S.L. Swamy; Anita Thakur; Alka Mishra; Sanjeev Bakshi; Amit Kumar; Muhammad Mohsin Altaf; Rupesh Kumar (Journal of Environmental Management, 2024)

MOFs coupled transition metals, graphene, and MXenes: Emerging electrocatalysts for hydrogen evolution reaction - Abdul Hanan; Muhammad Nazim Lakhan; Faiza Bibi; Amjad Khan; Irfan Ali Soomro; Altaf Hussain; Umair Aftab (Chemical Engineering Journal, 2024)

Season shapes the functional diversity of microbial carbon metabolism in mangrove soils of Hainan Island, China - Haihua Wang; Huaiyang Ke; Hongping Wu; Siyuan Ma; Muhammad Mohsin Altaf; Xiaoping Diao (CATENA, 2024)

Barriers affecting implementation of life cycle cost analysis in construction projects: SEM approach - Muhammad Altaf; Wesam Salah Alaloul; Muhammad Ali Musarat; Sherif Mostafa; Rodney Stewart; Ali Hussain; Muhammad Babar Ali Rabbani; Syed Saad; Syed Ammad (Innovative Infrastructure Solutions, 2024)

Engineering of metal organic framework (MOF) membrane for waste water treatment: Synthesis, applications and future challenges - Muhammad Umar Shahid; Tayyaba Najam; Mazharul Islam; Ahmed M. Hassan; Mohammed A. Assiri; Abdul Rauf; Aziz ur Rehman; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Journal of Water Process Engineering, 2024)

Nanoscale enhancements in perovskite-based photovoltaics - Sikandar Aftab; Xin Li; Sajjad Hussain; Muhammad Aslam; Altaf Hussain Rajpar; Abdullah G. Al-Sehemi (Chemical Engineering Journal, 2024)

Unraveling the mechanisms of cadmium toxicity in horticultural plants: Implications for plant health - Muhammad Ahsan Altaf; Safina Naz; Ravinder Kumar; Hasan Sardar; Muhammad Azher Nawaz; Awadhesh Kumar; Priyanka Lal; Riaz Ahmad; Faisal Hayat; Muneeb Ahmad Wani; Rahul Kumar Tiwari; Milan Kumar Lal (South African Journal of Botany, 2023)

Current understanding of boosting power of salicylic acid for abiotic stress tolerance in horticultural crops - Muhammad Ahsan Altaf; Rabia Shahid; Priyanka Lal; Riaz Ahmad; Faisal Zulfiqar; Awadhesh Kumar; Faisal Hayat; Ravinder Kumar; Milan Kumar Lal; Safina Naz; Rahul Kumar Tiwari (South African Journal of Botany, 2023)

Feeding ethogram of Antilochus coquebertii F. preying on Dysdercus koenigii - Adeel Mukhtar; Muhammad Usama Altaf; Muhammad Ikhlaq; Waqar Jaleel; Syed Muhammad Zaka; Asad Ali; Zahid Hanif (Journal of Asia-Pacific Entomology, 2023)

Seaweed Application Enhanced the Growth and Yield of Pea (Pisum sativum L.) by Altering Physiological Indices - Safina Naz; Hafiza Muniba Din Muhammad; Muhammad Ramzan; Bushra Sadiq; Riaz Ahmad; Saqib Ali; Abdulaziz Abdullah Alsahli; Muhammad Ahsan Altaf (Journal of Soil Science and Plant Nutrition, 2023)

Dinuclear gold(I) complexes based on carbene and diphosphane ligands: bis[2-(dicyclohexylphosphano)ethyl]amine complex inhibits the proteasome activity, decreases stem cell markers and spheroid viability in lung cancer cells - Naike Casagrande; Cinzia Borghese; Giuseppe Corona; Donatella Aldinucci; Muhammad Altaf; Adam A. A. Sulaiman; Anvarhusein A. Isab; Saeed Ahmad; Abdul Malik P. Peedikakkal (JBIC Journal of Biological Inorganic Chemistry, 2023)

A balancing act: Exploring the interplay between HSPs and osmoprotectants in temperature stress responses - Lopamudra Nayak; Milan Kumar Lal; Rahul Kumar Tiwari; Ravinder Kumar; Priyanka Lal; Ranjan Das; Biswaranjan Behera; Pankaj Thakur; Muhammad Ahsan Altaf; Awadhesh Kumar (South African Journal of Botany, 2023)

Consequences of vacuum evaporation on physicochemical properties, storage stability and in vitro digestion of fermented goat milk - Jiage Ma; Tianzhu Li; Nianxu Dou; Yanan Li; Qingyun Wang; Mengguo Wu; Yusi Miao; Jinzhe Li; Chengcheng Su; Lijun Chen; Muhammad Altaf Hussain; Juncai Hou; et al. (Food Control, 2023)

Life cycle cost analysis (LCCA) of construction projects: sustainability perspective - Muhammad Altaf; Wesam Salah Alaloul; Muhammad Ali Musarat; Abdul Hannan Qureshi (Environment, Development and Sustainability, 2023)

Synthesis of MXene-based single-atom catalysts for energy conversion applications - Muhammad Aizaz Ud Din; Syed Shoaib Ahmad Shah; Muhammad Sufyan Javed; Manzar Sohail; Aziz ur Rehman; Muhammad Altaf Nazir; Mohammed A. Assiri; Tayyaba Najam; Nanpu Cheng (Chemical Engineering Journal, 2023)

Diversity of arthropods in citrus orchards of Sargodha, Pakistan: Use of different trapping techniques - Muhammad Irfan Ullah; Muhammad Arshad; Asad Abdullah; Nimra Altaf; Syed Muhammad Ali Zahid; Muhammad Afzal (International Journal of Tropical Insect Science, 2023)

Melatonin Mitigates Salt-Induced Growth Inhibition Through the Regulation of Carbohydrate and Nitrogen Metabolism in Tomato Seedlings - Mohammad Shah Jahan; Guihua Li; Dasen Xie; Reham Farag; Md. Mahadi Hasan; Nadiyah M. Alabdallah; Nadi Awad Al-Harbi; Salem Mesfir Al-Qahtani; Muhammad Zeeshan; Jamal Nasar; Muhammad Ahsan Altaf; Md Atikur Rahman (Journal of Soil Science and Plant Nutrition, 2023)

Non-dairy prebiotics: Conceptual relevance with nutrigenomics and mechanistic understanding of the effects on human health - Rajni Devi; Eshita Sharma; Richa Thakur; Priyanka Lal; Awadhesh Kumar; Muhammad Ahsan Altaf; Brajesh Singh; Rahul Kumar Tiwari; Milan Kumar Lal; Ravinder Kumar (Food Research International, 2023)

Environmental sustainable: Biogenic copper oxide nanoparticles as nano-pesticides for investigating bioactivities against phytopathogens - Muhammad Aamir Manzoor; Iftikhar Hussain Shah; Irfan Ali Sabir; Ajaz Ahmad; Gadah Albasher; Afzal Ahmed Dar; Muhammad Ahsan Altaf; Awais Shakoor (Environmental Research, 2023)

Exogenous Application of Melatonin Improves the Growth and Productivity of Two Broccoli (Brassica oleracea L.) Cultivars Under Salt Stress - Hasan Sardar; Muhammad Arif Ramzan; Safina Naz; Sajid Ali; Shaghef Ejaz; Riaz Ahmad; Muhammad Ahsan Altaf (Journal of Plant Growth Regulation, 2023)

Phytohormones Mediated Modulation of Abiotic Stress Tolerance and Potential Crosstalk in Horticultural Crops - Muhammad Ahsan Altaf; Rabia Shahid; Ravinder Kumar; Muhammad Mohsin Altaf; Awadhesh Kumar; Latif Ullah Khan; Muhammad Saqib; Muhammad Azher Nawaz; Bushra Saddiq; Saraj Bahadur; Rahul Kumar Tiwari; Milan Kumar Lal; et al. (Journal of Plant Growth Regulation, 2023)

RETRACTED ARTICLE: Melatonin-Polyamine Interplay in the Regulation of Stress Responses in Plants - Rahul Kumar Tiwari; Ravinder Kumar; Milan Kumar Lal; Awadhesh Kumar; Muhammad Ahsan Altaf; Rajni Devi; Vikas Mangal; Safina Naz; Muhammad Mohsin Altaf; Abhijit Dey; Tariq Aftab (Journal of Plant Growth Regulation, 2023)

iPBS-retrotransposons variations: DNA fingerprinting and the evaluation of genetic diversity and population structure in international cowpea germplasm - Faheem Shehzad Baloch; Muhammad Tanveer Altaf; Mehmet Bedir; Muhammad Azhar Nadeem; Muhammed Tatar; Tolga Karaköy; Muhammad Aasim (Genetic Resources and Crop Evolution, 2023)

CR-NBEER: Cooperative-Relay Neighboring-Based Energy Efficient Routing Protocol for Marine Underwater Sensor Networks - Altaf Hussain; Tariq Hussain; Inam Ullah; Bahodir Muminov; Muhammad Zubair Khan; Osama Alfarraj; Amr Gafar (Journal of Marine Science and Engineering, 2023)
This paper proposes a Cooperative-Relay Neighboring-Based Energy-Efficient Routing (CR-NBEER) protocol with advanced relay optimization for MUSN. The utilization of the relay nodes, among all other sensor nodes, makes it possible to achieve node-to-node deployment. The proposed method focuses only on cooperation and relay optimization schemes. Both schemes have previously been implemented, and thus the proposed method represents the extended version of the Neighboring-Based Energy-Efficient Routing (NBEER) protocol. Path loss, end-to-end delay, packet delivery ratio, and energy consumption parameters were considered as part of the performance evaluation. The average performance was revealed based on simulations, where the overall average EED of Co-UWSN was measured to be 35.5 ms, CEER was measured to be 26.7 ms, NBEER was measured to be 27.6 ms, and CR-NBEER was measured to be 19.3 ms. Similarly, the overall EC of Co-UWSN was measured to be 10.759 j, CEER was measured to be 8.694 j, NBEER was measured to be 8.309 j, and CR-NBEER was measured to be 7.644 j. The overall average PDR of Co-UWSN was calculated to be 79.227%, CEER was calculated to be 66.73.464%, NBEER was calculated to be 85.82%, and CR-NBEER was calculated to be 94.831%. The overall average PL of Co-UWSN was calculated at 137.5 dB, CEER was calculated at 230 dB, NBEER was calculated at 173.8 dB, and CR-NBEER was calculated at 79.9 dB. Based on the simulations and evaluations, it was observed that the cooperation and relay optimization scheme outperformed previous schemes.

Impact of biochar amendments on copper mobility, phytotoxicity, photosynthesis and mineral fluxes on (Zea mays L.) in contaminated soils - Zainul Abideen; Hans-Werner Koyro; Faisal Zulfiqar; Anam Moosa; Sarwat Ghulam Rasool; Muhammad Zaheer Ahmad; Muhammad Ahsan Altaf; Nadia Sharif; Ali El-Keblawy (South African Journal of Botany, 2023)

Melatonin enhanced the heavy metal-stress tolerance of pepper by mitigating the oxidative damage and reducing the heavy metal accumulation - Muhammad Ahsan Altaf; Yuanyuan Hao; Huangying Shu; Muhammad Ali Mumtaz; Shanhan Cheng; Mohammed Nasser Alyemeni; Parvaiz Ahmad; Zhiwei Wang (Journal of Hazardous Materials, 2023)

Salinity Stress Tolerance in Solanaceous Crops: Current Understanding and Its Prospects in Genome Editing - Muhammad Ahsan Altaf; Sayanti Mandal; Biswaranjan Behera; Vikas Mangal; Safina Naz; Ravinder Kumar; Awadhesh Kumar; Mimosa Ghorai; Brajesh Singh; Abhijit Dey; Rahul Kumar Tiwari; Milan Kumar Lal; et al. (Journal of Plant Growth Regulation, 2023)

Exogenous melatonin alleviates cadmium-induced inhibition of growth and photosynthesis through upregulating antioxidant defense system in strawberry - Muhammad Saqib; Umbreen Shahzad; Faisal Zulfiqar; Rahul Kumar Tiwari; Milan Kumar Lal; Safina Naz; Mohammad Shah Jahan; Zoia Arshad Awan; Mohamed A. El-Sheikh; Muhammad Ahsan Altaf (South African Journal of Botany, 2023)

Characterization and comparison of structure, thermal and functional characteristics of various commercial pea proteins - Hong Sun; Jialu Sun; Nianxu Dou; Jinzhe Li; Muhammad Altaf Hussain; Jiage Ma; Juncai Hou (Food Bioscience, 2023)

Deciphering the melatonin-mediated response and signalling in the regulation of heavy metal stress in plants - Muhammad Ahsan Altaf; Nitin Sharma; Dipali Srivastava; Sayanti Mandal; Sandeep Adavi; Rupak Jena; Rakesh Kumar Bairwa; Abilash Valsala Gopalakrishnan; Awadhesh Kumar; Abhijit Dey; Milan Kumar Lal; Rahul Kumar Tiwari; et al. (Planta, 2023)

Artificial neural network and decision tree facilitated prediction and validation of cytokinin-auxin induced in vitro organogenesis of sorghum (Sorghum bicolor L.) - Muhammad Aasim; Seyid Amjad Ali; Muhammad Tanveer Altaf; Amjad Ali; Muhammad Azhar Nadeem; Faheem Shahzad Baloch (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Exploring the genetic diversity and population structure of upland cotton germplasm by iPBS-retrotransposons markers - Nurettin Baran; Flavien Shimira; Muhammad Azhar nadeem; Muhammad Tanveer altaf; Mehtap andirman; Faheem Shehzad Baloch; Mefhar Gültekin Temiz (Molecular Biology Reports, 2023)

Potential Breeding Strategies for Improving Salt Tolerance in Crop Plants - Muhammad Afzal; Salah El Sayed Hindawi; Salem Safer Alghamdi; Hussein H. Migdadi; Muhammad Altaf Khan; Muhammad Usama Hasnain; Muhammad Arslan; Muhammad Habib ur Rahman; Muhammad Sohaib (Journal of Plant Growth Regulation, 2023)
Salinity is one of the significant abiotic stresses that negatively affect plant production processes, growth, and development, which ultimately reduce yield. Plants adapt specific mechanisms to withstand saline conditions and activate diverse salt tolerance genes to counter osmotic and oxidative stresses induced by salinity. Genetic development in salinity tolerance is quite complex, while advancement has made less progress than expectation over the past few decades. Generating an explosion of genetics- and genomics-related information and technology in recent decades pledge to deliver innovative and advanced resources for the potential production of tolerant genotypes. Despite considerable progress in defining the primary salinity tolerance mechanisms, main obstacles are yet to be solved in the translation and incorporation of the resulting molecular knowledge into the plant breeding activities. Diverse approaches are proposed to enhance plant breeding efficacy to increase plant productivity in saline environments. Understanding the genetics of salt tolerance is a difficult task because multiple genes and pathways are involved. Important advances in tools and methods for updating and manipulating plant genomics knowledge provide detailed insights and dissect the salinity tolerance mechanism accomplished by the breeding goals. Genome-wide analyses (GWA) identify SNP variations and functional effects that appear to be the way of the future for developing salinity-tolerant plants. Gene discovery to manipulate the molecular mechanisms which underlie the complex phenotype of salinity tolerance methods, identification of genes, QTL, association mapping, linkage, and functional genomics, such as transcript identifying and proteins related to salinity, is necessary. The present analysis also discussed some of the opportunities and challenges, focusing on molecular breeding strategies used in conjunction with other crop development approaches to growing elite salt-tolerant lines.

A comprehensive and conceptual overview of omics-based approaches for enhancing the resilience of vegetable crops against abiotic stresses - Vikas Mangal; Milan Kumar Lal; Rahul Kumar Tiwari; Muhammad Ahsan Altaf; Salej Sood; Vijay Gahlaut; Ashish Bhatt; Ajay Kumar Thakur; Ravinder Kumar; Vinay Bhardwaj; Vinod Kumar; Brajesh Singh; et al. (Planta, 2023)

Functional characterization of transcriptional activator gene SIARRI in tomato reveals its role in fruit growth and ripening - Muhammad Fahad; Muhammad Tanveer Altaf; Amna Jamil; Abdul Basit; Muhammad Mudassir Aslam; Waqas Liaqat; Muhammad Nadeem Shah; Izhar Ullah; Heba I. Mohamed (Transgenic Research, 2023)

Optimisation of energy and life cycle costs via building envelope: a BIM approaches - Muhammad Altaf; Wesam Salah Alalaoul; Muhamamad Ali Musarat; Abdelaziz Abdelmahmoud Abdelaziz; Muhammad Jamaluddin Thaheem (Environment, Development and Sustainability, 2023)

Characterization of chitosan/α-lactalbumin nanocomplex particle and its encapsulation for retinol - Zhanmei Jiang; Jinzhe Li; Wei Chen; Muhammad Altaf Hussain; Xuan Wei; Akhunzada Bilawal; Juncai Hou (Food Bioscience, 2023)

Molecular Insights into the Role of Reactive Oxygen, Nitrogen and Sulphur Species in Conferring Salinity Stress Tolerance in Plants - Vikas Mangal; Milan Kumar Lal; Rahul Kumar Tiwari; Muhammad Ahsan Altaf; Salej Sood; Dharmendra Kumar; Vinay Bharadwaj; Brajesh Singh; Rajesh Kumar Singh; Tariq Aftab (Journal of Plant Growth Regulation, 2023)

Insight into microwave-assisted synthesis of the chitosan-MOF composite: Pb(II) adsorption - Humaira Gul Zaman; Lavania Baloo; Shamsul Rahman Kutty; Khalid Aziz; Muhammad Altaf; Aniqa Ashraf; Faissal Aziz (Environmental Science and Pollution Research, 2023)

Facile synthesis and comparative study of the enhanced photocatalytic degradation of two selected dyes by TiO2-g-C3N4 composite - Asma A. Alothman; Asif Ayub; Safa K. Hachim; Borhan Mustafa Mohammed; Farhat Hussain; Muhammad Altaf; Zainab Jawad Kadhim; Holya A. Lafta; Yasir S. Alnassar; Marwah A. Shams; Nada A. Almuhous; Mohamed Ouladsmane; et al. (Environmental Science and Pollution Research, 2022)

Protective Mechanisms of Melatonin Against Vanadium Phytotoxicity in Tomato Seedlings: Insights into Nutritional Status, Photosynthesis, Root Architecture System, and Antioxidant Machinery - Muhammad Ahsan Altaf; Rabia Shahid; Ming-Xun Ren; Latif Ullah Khan; Muhammad Mohsin Altaf; Mohammad Shah Jahan; Muhammad Azher Nawaz; Safina Naz; Sidra Shahid; Milan Kumar Lal; Rahul Kumar Tiwari; Muhammad Adnan Shahid (Journal of Plant Growth Regulation, 2022)

Dirty versus clean fuel for cooking in Pakistan: regional mapping and correlates - Tusawar Iftikhar Ahmad; Muhammad Atif Nawaz; Kokab Kiran; Vishal Dagar; Muhammad Azhar Bhatti; Altaf Hussain (Environmental Science and Pollution Research, 2022)

From source to sink: mechanistic insight of photoassimilates synthesis and partitioning under high temperature and elevated [CO2] - Milan Kumar Lal; Nitin Sharma; Sandeep B. Adavi; Eshita Sharma; Muhammad Ahsan Altaf; Rahul Kumar Tiwari; Ravinder Kumar; Awadhesh Kumar; Abhijit Dey; Vijay Paul; Brajesh Singh; Madan Pal Singh (Plant Molecular Biology, 2022)

NGS-driven molecular diagnosis of heterogeneous hereditary neurological disorders reveals novel and known variants in disease-causing genes - Ayaz Khan; Shixiong Tian; Muhammad Tariq; Sheraz Khan; Muhammad Safeer; Naimat Ullah; Nazia Akbar; Iram Javed; Mahnoor Asif; Ilyas Ahmad; Shahid Ullah; Humayoon Shafique Satti; et al. (Molecular Genetics and Genomics, 2022)

Synthesis, theoretical investigations and biological evaluation of ibuprofen drug hybrids - Adina Tatheer; Shahzad Murtaza; Naghmana Kausar; Ataf Ali Altaf; Samia Kausar; Safeer Ahmed; Shabbir Muhammad; Amjad Hussain (Medicinal Chemistry Research, 2022)

Correction to: Receptiveness of soil bacterial diversity in relation to soil nutrient transformation and canopy growth in Chinese fir monoculture influenced by varying stand density - Taimoor Hassan Farooq; Uttam Kumar; Yao Yan; Muhammad Saleem Arif; Awais Shakoor; Muhammad Tayyab; Paresh H. Rathod; Muhammad Mohsin Altaf; Pengfei Wu (Trees, 2022)

Insight into melatonin-mediated response and signaling in the regulation of plant defense under biotic stress - Rahul Kumar Tiwari; Milan Kumar Lal; Ravinder Kumar; Vikas Mangal; Muhammad Ahsan Altaf; Sanjeev Sharma; Brajesh Singh; Manoj Kumar (Plant Molecular Biology, 2022)

Assessment of genetic diversity among 131 safflower (Carthamus tinctorius L.) accessions using peroxidase gene polymorphism (POGP) markers - Mehtap Yildiz; Muhammad Tanveer Altaf; Faheem Shehzad Baloch; Metin Koçak; Gökhan Sadık; Cansu Kuzğun; Muhammad Azhar Nadeem; Fawad Ali; Mehmet Bedir; Murat Tunçtürk (Molecular Biology Reports, 2022)

Receptiveness of soil bacterial diversity in relation to soil nutrient transformation and canopy growth in Chinese fir monoculture influenced by varying stand density - Taimoor Hassan Farooq; Uttam Kumar; Yao Yan; Muhammad Saleem Arif; Awais Shakoor; Muhammad Tayyab; Paresh H. Rathod; Muhammad Mohsin Altaf; Pengfei Wu (Trees, 2022)

Salicylic Acid Induces Vanadium Stress Tolerance in Rice by Regulating the AsA-GSH Cycle and Glyoxalase System - Muhammad Mohsin Altaf; Xiao-ping Diao; Haihua Wang; Latif Ullah Khan; Atique ur Rehman; Awais Shakoor; Muhammad Ahsan Altaf; Taimoor Hassan Farooq (Journal of Soil Science and Plant Nutrition, 2022)

Strategic combination of metal–organic frameworks and C3N4 for expeditious photocatalytic degradation of dye pollutants - Ome Parkash Kumar; Muhammad Ahmad; Muhammad Altaf Nazir; Aqsa Anum; Muhammad Jamshaid; Syed Shoaib Ahmad Shah; Aziz Rehman (Environmental Science and Pollution Research, 2022)

Applicability of inter-primer binding site iPBS- retrotransposon marker system for the assessment of genetic diversity and population structure of Peruvian rosewood (Aniba rosaeodora Ducke) germplasm - Faheem Shehzad Baloch; Stalin Juan Vasquez Guizado; Muhammad Tanveer Altaf; Ilker Yüce; Yeter Çilesiz; Mehmet Bedir; Muhammad Azhar Nadeem; Rustu Hatipoglu; Juan Carlos Castro Gómez (Molecular Biology Reports, 2022)

Melatonin Mitigates Cadmium Toxicity by Promoting Root Architecture and Mineral Homeostasis of Tomato Genotypes - Muhammad Ahsan Altaf; Rabia Shahid; Ming-Xun Ren; Safina Naz; Muhammad Mohsin Altaf; Latif Ullah Khan; Milan Kumar Lal; Rahul Kumar Tiwari; Awais Shakoor (Journal of Soil Science and Plant Nutrition, 2022)

An Insight into Microbes Mediated Heavy Metal Detoxification in Plants: a Review - Rajni Devi; Biswaranjan Behera; Md Basit Raza; Vikas Mangal; Muhammad Ahsan Altaf; Ravinder Kumar; Awadhesh Kumar; Rahul Kumar Tiwari; Milan Kumar Lal; Brajesh Singh (Journal of Soil Science and Plant Nutrition, 2022)

Delineating Vanadium (V) Ecological Distribution, Its Toxicant Potential, and Effective Remediation Strategies from Contaminated Soils - Muhammad Mohsin Altaf; Xiao-ping Diao; Awais Shakoor; Muhammad Imtiaz; Atique-ur-Rehman; Muhammad Ahsan Altaf; Latif Ullah Khan (Journal of Soil Science and Plant Nutrition, 2022)

Melatonin Mitigates Nickel Toxicity by Improving Nutrient Uptake Fluxes, Root Architecture System, Photosynthesis, and Antioxidant Potential in Tomato Seedling - Muhammad Ahsan Altaf; Rabia Shahid; Ming-Xun Ren; Muhammad Mohsin Altaf; Mohammad Shah Jahan; Latif Ullah Khan (Journal of Soil Science and Plant Nutrition, 2021)

An in vitro antiviral activity of iodine complexes against SARS-CoV-2 - Imran Altaf; Muhammad Faisal Nadeem; Nadir Hussain; Muhammad Nawaz; Sohail Raza; Muhammad Abu bakr Shabbir; Muhammad Adnan Ashraf; Muhammad Asad Ali; Sohail Hassan; Muhammad Waqar Aziz; Nazish Matti; Muhammad Ashraf; et al. (Archives of Microbiology, 2021)

Effect of Vanadium on Growth, Photosynthesis, Reactive Oxygen Species, Antioxidant Enzymes, and Cell Death of Rice - Muhammad Mohsin Altaf; Xiao-ping Diao; Atique ur Rehman; Muhammad Imtiaz; Awais Shakoor; Muhammad Ahsan Altaf; Haseeb Younis; Pengcheng Fu; Muhammad Usman Ghani (Journal of Soil Science and Plant Nutrition, 2020)

Biogeochemical transformation of greenhouse gas emissions from terrestrial to atmospheric environment and potential feedback to climate forcing - Awais Shakoor; Fatima Ashraf; Saba Shakoor; Adnan Mustafa; Abdul Rehman; Muhammad Mohsin Altaf (Environmental Science and Pollution Research, 2020)

Efficient synthesis of 2,3-diarylbenzo[b]thiophene molecules through palladium (0) Suzuki–Miyaura cross-coupling reaction and their antithrombolyitc, biofilm inhibition, hemolytic potential and molecular docking studies - Nosheen Sial; Nasir Rasool; Komal Rizwan; Ataf Ali Altaf; Shaukat Ali; Ayesha Malik; Muhammad Zubair; Arusa Akhtar; Samia Kausar; Syed Adnan Ali Shah (Medicinal Chemistry Research, 2020)

Application of water quality index, synthetic pollution index, and geospatial tools for the assessment of drinking water quality in the Indus Delta, Pakistan - Ghulam Shabir Solangi; Altaf Ali Siyal; Muhammad Munir Babar; Pirah Siyal (Environmental Monitoring and Assessment, 2019)

Effects of selected synthetic insecticides on the total and differential populations of circulating haemocytes in adults of the red cotton stainer bug Dysdercus koenigii (Fabricius) (Hemiptera: Pyrrhocoridae) - Zahid Mahmood Sarwar; Mamuna Ijaz; Muhammad Altaf Sabri; Hasnain Yousaf; Muhammad Mohsan (Environmental Science and Pollution Research, 2018)

Nitrogen-regulated changes in total amino acid profile of maize genotypes having contrasting response to nitrogen deficit - Arshid Hussain Ganie; Altaf Ahmad; Peerzada Yasir Yousuf; Renu Pandey; Sayeed Ahmad; Ibrahim M Aref; Muhammad Iqbal (Protoplasma, 2017)

Understanding brassinosteroid-regulated mechanisms to improve stress tolerance in plants: a critical review - Fahim Nawaz; Muhammad Naeem; Bilal Zulfiqar; Asim Akram; Muhammad Yasin Ashraf; Muhammad Raheel; Rana Nauman Shabbir; Rai Altaf Hussain; Irfan Anwar; Muhammad Aurangzaib (Environmental Science and Pollution Research, 2017)

CDK5RAP2 interaction with components of the Hippo signaling pathway may play a role in primary microcephaly - Salil K. Sukumaran; Maria Stumpf; Sarah Salamon; Ilyas Ahmad; Kurchi Bhattacharya; Sarah Fischer; Rolf Müller; Janine Altmüller; Birgit Budde; Holger Thiele; Muhammad Tariq; Naveed Altaf Malik; et al. (Molecular Genetics and Genomics, 2017)

Dietary mycotoxins binders: a strategy to reduce aflatoxin m1 residues and improve milk quality of lactating Beetal goats - Haq Aman Ullah; Aneela Zameer Durrani; Muhammad Ijaz; Aqeel Javeed; Umer Sadique; Zahoor Ul Hassan; Altaf Ur Rahman; Muqader Shah; Irfan Khattak (Journal of Consumer Protection and Food Safety, 2016)

Salt-stress-responsive chloroplast proteins in Brassica juncea genotypes with contrasting salt tolerance and their quantitative PCR analysis - Peerzada Yasir Yousuf; Altaf Ahmad; Ibrahim M. Aref; Munir Ozturk; Hemant; Arshid Hussain Ganie; Muhammad Iqbal (Protoplasma, 2016)

OpenDA-NEMO framework for ocean data assimilation - Nils van Velzen; Muhammad Umer Altaf; Martin Verlaan (Ocean Dynamics, 2016)

Toxicity Appraisal of Untreated Dyeing Industry Wastewater Based on Chemical Characterization and Short Term Bioassays - Muhammad Furqan Akhtar; Muhammad Ashraf; Aqeel Javeed; Aftab Ahmad Anjum; Ali Sharif; Ammara Saleem; Bushra Akhtar; Abdul Muqeet Khan; Imran Altaf (Bulletin of Environmental Contamination and Toxicology, 2016)

Foliar NK application mitigates drought effects in sunflower (Helianthus annuus L.) - Rai Altaf Hussain; Rashid Ahmad; Fahim Nawaz; Muhammad Yasin Ashraf; Ejaz Ahmad Waraich (Acta Physiologiae Plantarum, 2016)

Pharmaceutical wastewater being composite mixture of environmental pollutants may be associated with mutagenicity and genotoxicity - Ali Sharif; Muhammad Ashraf; Aftab Ahmed Anjum; Aqeel Javeed; Imran Altaf; Muhammad Furqan Akhtar; Mateen Abbas; Bushra Akhtar; Ammara Saleem (Environmental Science and Pollution Research, 2016)

Salt stress-induced modulations in the shoot proteome of Brassica juncea genotypes - Peerzada Yasir Yousuf; Altaf Ahmad; Arshid Hussain Ganie; Muhammad Iqbal (Environmental Science and Pollution Research, 2016)

FRET-based genetically-encoded sensors for quantitative monitoring of metabolites - Mohd. Mohsin; Altaf Ahmad; Muhammad Iqbal (Biotechnology Letters, 2015)

Synthesis, characterization and theoretical calculations of (1,2-diaminocyclohexane)(1,3-diaminopropane)gold(III) chloride complexes: in vitro cytotoxic evaluations against human cancer cell lines - Said S. Al-Jaroudi; Muhammad Altaf; Abdulaziz A. Al-Saadi; Abdel-Nasser Kawde; Saleh Altuwaijri; Saeed Ahmad; Anvarhusein A. Isab (BioMetals, 2015)

Photosynthesis and growth responses of mustard (Brassica juncea L. cv Pusa Bold) plants to free air carbon dioxide enrichment (FACE) - Kamal Ruhil; Sheeba; Altaf Ahmad; Muhammad Iqbal; Baishnab C. Tripathy (Protoplasma, 2015)

Synthesis, spectroscopic characterization, electrochemical behavior and computational analysis of mixed diamine ligand gold(III) complexes: antiproliferative and in vitro cytotoxic evaluations against human cancer cell lines - Said S. Al-Jaroudi; M. Monim-ul-Mehboob; Muhammad Altaf; Abdulaziz A. Al-Saadi; Mohammed I. M. Wazeer; Saleh Altuwaijri; Anvarhusein A. Isab (BioMetals, 2014)

Modulation of Reproductive Behaviors by Non-Host Volatiles in the Polyphagous Egyptian Cotton Leafworm, Spodoptera littoralis - Muhammad Binyameen; Altaf Hussain; Fatemeh Yousefi; Göran Birgersson; Fredrik Schlyter (Journal of Chemical Ecology, 2013)

Cytotoxic, phytotoxic, and mutagenic appraisal to ascertain toxicological potential of particulate matter emitted from automobiles - Khaleeq Anwar; Sohail Ejaz; Muhammad Ashraf; Imran Altaf; Aftab Ahmad Anjum (Environmental Science and Pollution Research, 2013)

Erratum to: Nitrogen-efficient rice cultivars can reduce nitrate pollution - Khalid Rehman Hakeem; Altaf Ahmad; Muhammad Iqbal; Salih Gucel; Munir Ozturk (Environmental Science and Pollution Research, 2012)

Simultaneous perturbation stochastic approximation for tidal models - Muhammad Umer Altaf; Arnold W. Heemink; Martin Verlaan; Ibrahim Hoteit (Ocean Dynamics, 2011)

Nitrogen-efficient rice cultivars can reduce nitrate pollution - Khalid Rehman Hakeem; Altaf Ahmad; Muhammad Iqbal; Salih Gucel; Munir Ozturk (Environmental Science and Pollution Research, 2011)

Sulfur starvation and restoration affect nitrate uptake and assimilation in rapeseed - Gurjeet Kaur; Ruby Chandna; Renu Pandey; Yash Pal Abrol; Muhammad Iqbal; Altaf Ahmad (Protoplasma, 2011)

Uptake-related parameters as indices of phytoremediation potential - Hema Diwan; Altaf Ahmad; Muhammad Iqbal (Biologia, 2010)

Cytology of infection of Fusarium mangiferae Britz in different malformed reproductive parts of mango - Zafar Iqbal; Sohail Hameed; Muhammad Akbar Anjum; Altaf Ahmad Dasti; Ahmad Saleem (European Journal of Plant Pathology, 2010)

Variability in Indian bread wheat (Triticum aestivum L.) varieties differing in nitrogen efficiency as assessed by microsatellite markers - Ruby Chandna; Sarika Gupta; Altaf Ahmad; Muhammad Iqbal; Manoj Prasad (Protoplasma, 2010)

Phytoremediation of Heavy Metals: Physiological and Molecular Mechanisms - Ruqaya Jabeen; Altaf Ahmad; Muhammad Iqbal (The Botanical Review, 2009)

Genotypic Variation in the Phytoremediation Potential of Indian Mustard for Chromium - Hema Diwan; Altaf Ahmad; Muhammad Iqbal (Environmental Management, 2008)